2009
DOI: 10.1353/lan.0.0110
|View full text |Cite
|
Sign up to set email alerts
|

The Present of the English Future: Grammatical Variation and Collocations in Discourse

Abstract: We use the variationist method to elucidate the expression of future time in English, examining multiple grammaticalization in the same domain ( will and going to ). Usage patterns show that the choice of form is not determined by invariant semantic readings such as proximity, certainty, willingness, or intention. Rather, particular instances of each general construction occupy lexical, syntactic, and pragmatic niches. While putative differences in meaning are largely neutralized in discourse, grammaticalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
100
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(118 citation statements)
references
References 101 publications
15
100
1
2
Order By: Relevance
“…On the other hand, the much less frequent negative clause contexts act as an important structural entry point for the diffusion of the emerging variants (16th c.: FW .28; 18th c.: FW .31), which confirms the important role of negative polarity identified in other processes of grammaticalization and syntactic change (Torres Cacoullos & Walker 2009;Tagliamonte et al 2014). …”
Section: Clausal Polarity and Typesupporting
confidence: 57%
“…On the other hand, the much less frequent negative clause contexts act as an important structural entry point for the diffusion of the emerging variants (16th c.: FW .28; 18th c.: FW .31), which confirms the important role of negative polarity identified in other processes of grammaticalization and syntactic change (Torres Cacoullos & Walker 2009;Tagliamonte et al 2014). …”
Section: Clausal Polarity and Typesupporting
confidence: 57%
“…Although the graduate learners and NSs shared with the other groups the pattern of using LFs more with a distant future and the PI more with an immediate future, these differences did not yield significance. Part of the explanation can be found in the results of prior research, which has found that the PI is at times deployed at maximal temporal distances, often because it also contains adverbial modification at that distance (e.g., Torres Cacoullos & Walker, , for English). Furthermore, for a narrative effect, use of the present provides a proximity that can be implemented even with distant pasts or futures cross‐linguistically, as with the historical present for past actions and the use of present for future (e.g., Bybee et al., , p. 83).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these, we will also investigate some variables, such as clause structure and prefabricated expressions ("frequent collocations" in the terms of Torres-Cacoullos and Walker 2009), which have been shown to be significant in conditioning variation in some studies of will versus be going to (e.g. Szmrecsanyi 2003, Torres-Cacoullos andWalker 2009). The same variables will form the basis of our analysis of DECTE.…”
Section: Constraints Conditioning Variationmentioning
confidence: 99%